The relationship between factor of motivation and employee performance : the study of manufacturing industry in my sutera sdn.bhd pengkalan chepa, Kelantan - Norhumaira, Juhai (2013)
Motivation seems to be one of the most important tools in manufacturing industry. Motivational factors play an important role in increasing employee performance. Employee‟s performance in return can help in improving productivity of company. To maintain effectiveness and development, managers need to adopt a clear and attainable motivational system in their organization. Organizations design motivation systems to encourage employees to perform in the most effective way but also to attract potential candidates. The key to create the efficient motivation system is an answer to the question what really motivate employees. The purpose of this study is to find which motivation factors are seen as the most important by employees considered as future motivation persons. The second aimed is to identify the relationships between factor motivation and employees performance in manufacturing company at My Sutera Sdn.Bhd, Pengkalan Chepa, Kota Bharu. The sample of this study consisted of 120 employees from 200 populations of employees at that company. The real sample size is 127 but only 120 that I get the information because some of the questionnaire that I distributed are missing and not complete. Its consist (16 male and 104 female). This research used motivation questionnaire as instruments for data collection. This research used the SPSS program version 13 for data analysis. Different statistical procedures were used for data analysis including, percentage, mean, descriptive statistic, normality test, and Pearson correlation. The results showed that the most important factor of motivation is training which the highest value (3.5233), second is recognition (3.4517), then reward (3.4490) and the last is peer group (3.3917). Besides that, the result about relationship between factor motivation and employees performance are showed all factor has significant relationship with employee‟s performance.